Protective Role of mPGES-1 (Microsomal Prostaglandin E Synthase-1)–Derived PGE2 (Prostaglandin E2) and the Endothelial EP4 (Prostaglandin E Receptor) in Vascular Responses to Injury. Issue 5 (May 2018) - Hao, Huifeng; Hu, Sheng; Wan, Qing; Xu, Chuansheng; Chen, Hong; Zhu, Liyuan; Xu, Zhenyu; Meng, Jian; Breyer, Richard M.; Li, Nailin; Liu, De-Pei; FitzGerald, Garret A.; et al.
Abstract : Objective—: Deletion of mPGES-1 (microsomal prostaglandin E synthase-1)—an anti-inflammatory target alternative to COX (cyclooxygenase)-2—attenuates injury-induced neointima formation in mice. This is attributable to the augmented levels of PGI2 (prostacyclin)—a known restraint of the vascular response to injury, acting via IP (I prostanoid receptor). To examine the role of mPGES-1–derived PGE2 (prostaglandin E2 ) in vascular remodeling without the IP. Approach and Results—: Mice deficient in both IP and mPGES-1 (DKO [double knockout] and littermate controls [IP KO (knockout)]) were subjected to angioplasty wire injury. Compared with the deletion of IP alone, coincident deletion of IP and mPGES-1 increased neointima formation, without affecting media area. Early pathological changes include impaired reendothelialization and increased leukocyte invasion in neointima. Endothelial cells (ECs), but not vascular smooth muscle cells, isolated from DKOs exhibited impaired cell proliferation. Activation of EP (E prostanoid receptor) 4 (and EP2, to a lesser extent), but not of EP1 or EP3, promoted EC proliferation. EP4 antagonism inhibited proliferation of mPGES-1–competent ECs, but not of mPGES-1–deficient ECs, which showed suppressed PGE2 production. EP4 activation inhibited leukocyte adhesion to ECs in vitro, promoted reendothelialization, and limited neointima formation post-injury in the mouse. Endothelium-restricted deletion of EP4 in mice suppressed reendothelialization, increased neointimal leukocytes, and exacerbated neointimal formation. Conclusions—: Removal of the IP receptors unmasks a protective role of mPGES-1–derived PGE2 in limiting injury-induced vascular hyperplasia. EP4, in the endothelial compartment, is essential to promote reendothelialization and restrain neointimal formation after injury. Activating EP4 bears therapeutic potential to prevent restenosis after percutaneous coronary intervention. Abstract : Supplemental Digital Content is available in the text.